Synergistic effect of hybrid fillers/ polydimethylsiloxane composites on enhancing thermal conductivity. (December 2021) - Yang, Chii-Rong; Chen, Chang-Da; Cheng, Chia; Shi, Wen-Hao; Chen, Po-Han; Teng, Tun-Ping
Abstract: We used the atmospheric plasma process (APP) to modify the particles of spherical aluminum nitride (AlN), graphene (GN), and multi-walled carbon nanotubes (MWCNTs) in different size. Then, the modified AlN particles, GN, and MWCNTs were added in polydimethylsiloxane (PDMS) as fillers to form hybrid fillers/PDMS composites. The thermal conductivity ( k ) of the test samples was measured using an instrument that referred to the ASTM D5470-06 standard. Finally, at temperature of the room to 600 °C for the sample, the highest k and pure PDMS were tested by thermogravimetric analysis. The results show that the fillers have good combination and dispersion in the PDMS, which promotes the filler to be overlapped and arranged more closely, resulting in a synergistic effect and a significant increase in the k of the hybrid filler/PDMS composites. The configuration conditions of filler with the highest k are 60 wt% spherical AlN particles, 2 wt% GN, and 2 wt% MWCNTs, and its k can reach 7.02 W/m-K. Furthermore, the hybrid fillers/PDMS with the highest k prepared in this study has superior feasibility under the operating temperature range of 200 °C in addition to a superior k value.